2012
DOI: 10.1007/s00405-012-2254-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of thymoquinone against cisplatin-induced ototoxicity

Abstract: The aim of this study was to investigate the potential protective effect of thymoquinone against cisplatin-induced ototoxicity. This study is a prospective, controlled experimental animal study. Experiments were performed on 30 healthy female Sprague-Dawley rats. Thirty animals were divided into three groups of 10 animals each. Group 1 received an intraperitoneal (i.p.) injection of cisplatin 15 mg/kg. Group 2 received i.p. thymoquinone 40 mg/kg/day for 2 days prior to cisplatin injection and third day i.p. ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…However, some of these may interfere with the beneficial effects of platinum drugs [179][180][181][182][183] . Moreover, none of these reagents has been tested in humans.…”
Section: Pharmacological Approachesmentioning
confidence: 99%
“…However, some of these may interfere with the beneficial effects of platinum drugs [179][180][181][182][183] . Moreover, none of these reagents has been tested in humans.…”
Section: Pharmacological Approachesmentioning
confidence: 99%
“…In another study, it has been demonstrated that cisplatin may lead to production of excess amounts of free radicals, and destructive changes in DNA. [13] Apoptosis is a controlled, and programmed cell death which may become apparent under normal growth and development or as a component of a response to exposure to radiation, toxins or ischemia. Apoptosis has been asserted probably as main outcome of cisplatin-induced toxicity.…”
Section: Bcl-2 Baxmentioning
confidence: 99%
“…Available evidence demonstrate that increases in ROS production, and expression of endogenous antioxidant molecules support cisplatin toxicity. [11][12][13][14] As a result of OS, priorly, apoptotic cell loss occurs. [15] Cisplatin may produce reactive oxygen species, and inhibit antioxidant enzymes in normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Many antioxidant agents have been used to prevent cisplatin-induced ototoxicity in experimental animal or clinical trials [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][33][34][35][36][37]. Kizilay et al [5] performed an experimental study on the protective effect of caffeic acid phenethyl ester (CAPE) on cisplatin ototoxicity and reported that CAPE may have a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Amelioration of cisplatin-induced ototoxicity has been demonstrated in studies, with many reporting on the protective effect of antioxidant agents, such as caffeic acid phenethyl ester [5], D-methionine [6], dexamethasone [7], neurotropines [8], flunarizine [9], amifostine [10], N-acetyl cysteine [11,12], erdosteine [13], salicylates [14], gingko biloba extract [15], allopurinol, ebselen [16], resveratrol [4,17], thymoquinone [18], betaglucan [19], and lycopene [20].…”
Section: Introductionmentioning
confidence: 99%